Effects of somatostatin on renal function in cirrohotic patients with ascites - Yusuf UZUN,; Abdulkadir DÖKMECİ,; Hasan ÖZKAN,; Hakan BOZKAYA,; Özden UZUNALİMOĞLU, (Turkish Journal of Gastroenterology, 2019)
-